x^2 + 11x + 30
2007-02-28 03:10:32
·
answer #1
·
answered by fcas80 7
·
0⤊
0⤋
(x+5)(x+6) = x*x + 5*x + x*6 + 5*6 = x^2 + 11x + 30
2007-02-28 11:30:49
·
answer #2
·
answered by Donald Duck 6
·
0⤊
0⤋
Are you looking for x? If so, the only way to find it would be to know what the answer to the equation is. (eg. (x + 5)(x + 6) = 50) In the example, you would divide the both sides by (x + 5) which turns the left side into (x + 6)/1 (or just x + 6 and the right side turns to 50/(x + 5). Then subtract 6 from both sides, so that the right side becomes just x. So then x = (50/x + 5) - 6. After that I get stuck too. Hopefully I've pointed you in the right direction, though. Good luck.
2007-02-28 11:19:22
·
answer #3
·
answered by Stacy Cuccia 3
·
0⤊
0⤋
You need to multiply each element of each bracket together.
(x+5)(x+6) = x*x + 5*x + x*6 + 5*6 = x^2 + 11x + 30
2007-02-28 11:16:04
·
answer #4
·
answered by kinvadave 5
·
0⤊
0⤋
(x + 5).(x + 6) = x² + 6x + 5x + 30 = x² + 11x + 30
2007-02-28 11:19:53
·
answer #5
·
answered by Como 7
·
0⤊
0⤋
x = -1
2007-02-28 11:16:21
·
answer #6
·
answered by liznjames_08 2
·
0⤊
0⤋
x^2 + 11x + 30
2007-02-28 11:12:58
·
answer #7
·
answered by physicist 4
·
0⤊
0⤋
x^2 +11x + 30
2007-02-28 11:11:20
·
answer #8
·
answered by ignoramus 7
·
0⤊
0⤋
x^2+11x+30
2007-02-28 11:11:22
·
answer #9
·
answered by raj 7
·
0⤊
0⤋
=X^2+6X+5X+30
=X^2+11X+30
Pretty simple, huh? :)
2007-02-28 11:16:55
·
answer #10
·
answered by KittyLover 1
·
0⤊
0⤋